2020
DOI: 10.5194/acp-2020-330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-deliquescent water uptake in deposited nanoparticles observed with in situ ambient pressure X-ray photoelectron spectroscopy

Abstract: Abstract. We study the adsorption of water onto deposited inorganic sodium chloride and organic malonic acid and sucrose nanoparticles at ambient water pressures corresponding to relative humidities (RH) from 0 to 16 %. To obtain information about water uptake at conditions where not accessible with typical aerosol instrumentation, we use surface-sensitive ambient pressure X-ray photoelectron spectroscopy (APXPS), which has a detection sensitivity from parts per thousand. Our results show that water is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been applied to a variety of non-supported microparticles and NPs, such as electrodynamically trapped SiO 2 , 22 Au-coated SiO 2 , 23 levitating droplets, 24 in situ generated soot, 25 and atomized salt solutions. 26,27 Compared to X-ray-based photoelectron and photoabsorption spectroscopies nowadays available also with RH control for deposited nanoparticles 28 and salt surfaces, 29 using a continuously renewed nanoparticle beam we ensure that there are no substrate effects, radiation induced changes, and no further growth or change of particles aer deposition. Here we apply XAS to study the hydration state of CaCl 2 -NPs by comparing XAS spectra of NPs generated at different RH to those obtained from water in different states, aqueous CaCl 2 solution, and solid CaCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to a variety of non-supported microparticles and NPs, such as electrodynamically trapped SiO 2 , 22 Au-coated SiO 2 , 23 levitating droplets, 24 in situ generated soot, 25 and atomized salt solutions. 26,27 Compared to X-ray-based photoelectron and photoabsorption spectroscopies nowadays available also with RH control for deposited nanoparticles 28 and salt surfaces, 29 using a continuously renewed nanoparticle beam we ensure that there are no substrate effects, radiation induced changes, and no further growth or change of particles aer deposition. Here we apply XAS to study the hydration state of CaCl 2 -NPs by comparing XAS spectra of NPs generated at different RH to those obtained from water in different states, aqueous CaCl 2 solution, and solid CaCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The same cooling channel can also be used to cool the samples below RT, by flowing a cold gas or liquid through the channel. So far it has been demonstrated that by flowing cold nitrogen gas through the channel it is possible to cool the samples down to À30 C. Cooling the samples further extends the available sample environments and is useful, for instance, in the cases where controlling the relative humidity inside the cell is desired (Lin et al, 2021). The same cooling could also be used for the investigations of ice on surfaces.…”
Section: Standard Cellmentioning
confidence: 99%